2009
DOI: 10.2134/agronj2009.0017
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Regulator Effects on Balancing Vegetative and Reproductive Phases in Alfalfa Seed Yield

Abstract: The use of plant growth regulators (PGRs) has opened new prospects for increased seed production in grasses and legumes, but little information is available on the effects of PGRs on alfalfa (Medicago sativa L.) seed production. This study was conducted to evaluate the effects of applying chlormequat chloride (CCC) (2‐chloroethyl‐trimethyl‐ammonium chloride) in combination with five PGRs {naphthylacetic acid [1‐naphthylacetic acid], sodium nitrophenolate, gibberellic acid 3 [2,4a,7‐trihydroxy‐1‐methyl‐8‐methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
7
0
1
Order By: Relevance
“…This, when coupled with the ABA-and SA-induced mobilization of metabolites to the developing fruits during the drought conditions when current available photoassimilates was strongly limited, may have stimulated the switch from vegetative to reproductive growth and, hence, caused an increase in fruit yield, as observed herein. There was also reported that PGRs increased the yield and harvest index, but did not affect aboveground biomass of alfalfa plants (Zhang et al, 2009).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This, when coupled with the ABA-and SA-induced mobilization of metabolites to the developing fruits during the drought conditions when current available photoassimilates was strongly limited, may have stimulated the switch from vegetative to reproductive growth and, hence, caused an increase in fruit yield, as observed herein. There was also reported that PGRs increased the yield and harvest index, but did not affect aboveground biomass of alfalfa plants (Zhang et al, 2009).…”
Section: Resultsmentioning
confidence: 94%
“…From the other substances, which share some characteristics with the classical hormones, have also been included (i.e., SA and jasmonates). PGRs can improve the physiological efficiency, including photosynthetic ability, enhance the partition of accumulates from source and sink, and reduce vegetative growth and improve yield of the field crops (Zhang et al, 2009). However, effect of PGRs on yield and plant development varied from species to species (Rademacher, 2015).…”
mentioning
confidence: 99%
“…The nitrophenolates had also marked effects on seed production and quality, fruit abscission, plant growth and some metabolic events in plants. These effects were documented by Sharma et al (1990) on soybean, Bynum et al (2007) on cotton, Chen (2008) on Camellia oleifera, Zhanga et al (2009) on alfalfa, Genesoylu (2009) and Dianaquiraman et al (2010) on cotton, andOgorek et al (2011) on fusarium.…”
Section: Introductionmentioning
confidence: 82%
“…За даними Bolanos-Aguilar et al [17], дослідження в галузі генетики та селекції показали, що прогрес у досягненні більш високого врожаю насіння люцерни обмежений. З іншого боку, оптимальне використання мінерального живлення [18][19][20][21], застосування поліфункціональних багатокомпонентних бактеріальних препаратів [22][23][24][25][26][27][28][29][30], регуляторів росту [31], запилювачів [32; 33], відстань між рядами, кількість насіння, що використовується для сівби, і площа жив-лення рослин [34] мають значний вплив на формування компонентів продуктивності та формування врожаю, здається, що це найкращий шлях для досягнення більш високої і стабільної насіннєвої продуктивності [35; 36].…”
Section: постановкаunclassified